Characterisation of Mechanical Properties, Damage Progression and Fracture Modes of Recycled Aluminium Alloys AA6061 Reinforced Alumina Oxide - Maat, Norzarina; Mohd Nor, Mohd Khir; Ho, Choon Sin (International Journal of Integrated Engineering, 2021)
Characterisation of the deformation behaviour of recycled aluminium alloy reinforced alumina oxide in terms of mechanical properties, damage progression and fracture mode is investigated via the Uniaxial Tensile Test in this manuscript. The tests are carried out at room temperature at strain rates of 6X10-3s-1, 6X10-2s-1, and 6X10-1s-1. Stress-strain curves and microstructural analysis are used to examine tensile behaviour, damage progression, and fracture mechanism. The primary form of aluminium alloy AA6061 was compared to the stress-strain curve analysis. It has been observed that when the strain rate increases, the flow stress increases. Field-Emission Scanning Electron Microscopy (FESEM) is used to analyse the damage progression, including fracture mode and continued with a close review on voids quantity and size using Image J Tooling Software. The results show that increasing strain rate increases the number of voids. In general, the recycled AA6061 reinforced Alumina Oxide exhibits strain-rate dependency behaviour. In terms of the fracture mode, an apparent necking develops around the fracture area in primary specimen. Necking, on the other hand, is less apparent in the recycled specimen. Due to alumina characteristics (ceramic), which promote fracture when necking begins to occur. The ductility of the recycled specimen is degraded after going through the recycling operations. With an increase in strain rate, the flow stress and damage evolution become more pronounced. This work contributes valuable information that can be established in various engineering applications significantly to improve the existing recycling process